Teachers’ Gender Influence on Adoption and Use of Information and Communication Technology in Public Secondary Schools in Kenya - Oduor , Hellen Nekesa; Ayiro , Laban; Boit , John (African Journal of Education,Science and Technology (AJEST), 2018)
The purpose of this study was to establish the influence of teachers’ gender on adoption and use of Information and Communication Technology (ICT) in public secondary schools in Kenya. The objective was to: Determine the effect of gender on adoption and use of ICT in public secondary schools. Target population was 30,080 teachers under the ICT Economic Stimulus Programme (ESP). Simple random sampling technique was used to obtain 244 teachers. A mixed methods research design inclined towards quantitative strategy was adopted. The study was informed by pragmatic philosophical paradigm. Teachers’ gender constituted the independent variable, while adoption and use of ICT was the dependent variable. Data was collected by closed-ended questionnaire and interview schedule, organized and presented using frequency, mean and standard deviation tables. The hypothesis was tested by Pearson’s correlation coefficient. The number of male teachers and female teachers was 162 and 82 respectively. However, the use of computers by males had a mean of 3.679 and the female 3.4756 on a Likert scale of 1 to 5. The use of Liquid Crystal Display (LCD) projectors had a mean of 2.5802 for male teachers and 2.4390 for female teachers. Use of printers had a mean of 4.1605 for males and 3.914 for females. Also, use of internet had a mean of 3.3765 for males and a mean of 3.353 for females. All the responses on items relating to adoption were between 4.0 and 5.0 which would mean agreeing and strongly agreeing respectively, hence the teachers were not using ICT in secondary schools. The hypothesis, HO1: There was no significant relationship between gender with adoption and use of ICT, male teachers ranked higher than female teachers on the use of IT for instructional support with mean ranks of 124.03 and 119.47 respectively after testing using Mann Whitney U test. The p value was 0.624 which was greater than P = 0.05 hence the hypothesis indicated that there was no statistically significant relationship between gender with adoption and use of ICT. Findings of this study will provide a framework which will assist school managers make decisions on how to adopt and use ICT in schools. The study recommended that education stakeholders should give clear information on the adoption and use of ICT in secondary schools and establish the source of funds for maintenance, repairs and further acquisition of the necessary infrastructure amid enrolment explosion in public secondary schools. Also, teachers need to be empowered through both pre- service and continuous in-service training.